Potensi Minyak dan Tepung Ikan Tuna (Thunnus albacares) Hasil Perikanan Tangkap Provinsi Bengkulu Sebagai Bahan Fortifikasi Pangan Bergizi - Wica Elvina; Kurnia Dewiani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2026)
Tuna fish (Thunnus albacares.) is one of the capture fisheries commodities with significant potential to be developed as a nutritious food ingredient to support food diversification. This study aimed to evaluate the potential of tuna fish oil and tuna fish flour derived from capture fisheries in Bengkulu Province as ingredients for nutritious food formulations through yield and chemical characteristic analyses. The study was conducted by processing tuna into fish oil using an oven-heating method at 100°C for 6 hours, while the residual solid from the oil extraction process was further processed into fish flour using a food dehydrator at 90°C for 8 hours. The analyzed parameters included the yield of fish oil and fish flour, moisture content, free fatty acids (FFA), protein content, fat content, and carbohydrate content. The results showed that the yield of tuna fish oil was 10.46%, while the yield of tuna fish flour reached 26.75%. Tuna fish oil had a moisture content of 0.47% and an FFA value of 0.86%, both of which met fish oil quality standards. Meanwhile, tuna fish flour contained 9.14% moisture, 53.45% protein, 6.92% fat, and 22.63% carbohydrates. These findings indicate that tuna fish oil and fish flour have strong potential as raw materials for functional food and food fortification due to their high protein content and omega-3 fatty acids, which provide important health benefits. The combined utilization of tuna fish oil and fish flour has the potential to produce food products with more complete nutritional value and higher added value in supporting local resource-based food diversification.